2013
DOI: 10.1021/ol402150m
|View full text |Cite
|
Sign up to set email alerts
|

The Backbone N-(4-Azidobutyl) Linker for the Preparation of Peptide Chimera

Abstract: Cu(I)-catalyzed 1,3-dipolar cycloaddition with mPEG 2000 -NH-CO-CH 2 CH 2 -alkyne …..…..…….. 18 N-acylation with mPEG 2000 -CH 2 CH 2 -COOSu ……………………………………………………….. 19 Reductive N-alkylation with mPEG 2000 -CH 2 CH 2 -CHO…………..……..…………………………… 20 3. NMR characterization of cyclo[RGDfNMeV] (1) and cyclo[RGDf(N-CH 2 CH 2 CH 2 CH 2 N 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
0
16
0
2
Order By: Relevance
“…[37] N-methylation can also be substituted with an N-(4-azido butyl) group to induce cis-amide bond formation. [38] The triazole group formed by click chemistry has also been utilized as a turn-inducing cis-proline mimetic. [39] Pseudo-prolines [40] and heterocycles [41] have been used to introduce turn structures into cyclic peptides.…”
Section: Cyclic Peptide Turnsmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] N-methylation can also be substituted with an N-(4-azido butyl) group to induce cis-amide bond formation. [38] The triazole group formed by click chemistry has also been utilized as a turn-inducing cis-proline mimetic. [39] Pseudo-prolines [40] and heterocycles [41] have been used to introduce turn structures into cyclic peptides.…”
Section: Cyclic Peptide Turnsmentioning
confidence: 99%
“…This includes the integrins, which are an important class of surface receptors involved in cell-cell and cell-matrix interactions. Highly potent and selective inhibitors have been developed through (37); R = AcNH (3D53 or PMX53), [44 ] R = H (3D624 or PMX205); [45] b) helix bundle of human C5a (38) showing activating C-terminus (bold); c) NMR structures (39) of peptides en route to 37. [44] Constrained Cyclic Peptides Angewandte Chemie constraining the pharmacophore sequence RGD into small cyclic peptides presenting this motif in a turn conformation.…”
Section: Cyclic Peptide Turnsmentioning
confidence: 99%
“…In another study, they synthesized an N ‐(4‐azidobutylated) analog of cilengitide, and conjugated it with a polyethylene glycol (PEG) chain through several chemical transformations. They thereby showed that the introduction of an N ‐(4‐azidobutyl) group is a valuable strategy to allow conjugation in peptides that do not have attachment sites and/or are not amenable to side‐chain modification whilst preserving biological activity . Regarding the preparation of N ‐substituted peptides through combinatorial approaches, there is one example reported.…”
Section: Classes Of Backbone N‐substituted Peptidesmentioning
confidence: 99%
“…A possible method to do so is by reductive alkylation with a suitable aldehyde (Figure , path A). Conditions for reductive N α ‐alkylation that render a high yield of N ‐monoalkylated product are reported, but they have to be optimized in each synthesis in order to minimize N,N ‐dialkylation and maintain an acceptable conversion . Another possibility to introduce the N‐ substituent is by activating the α‐amino group of the resin‐bound peptide as a sulfonamide, followed by N α ‐alkylation, and finally removal of the sulfonamide group (Figure , paths A and B).…”
Section: Synthetic Strategies For Backbone N‐substituted Peptidesmentioning
confidence: 99%
“…[37] Statt der N-Methylierung kann auch eine N-4-Azidobutylgruppe den gleichen Zweck erfüllen. [38] Auch die Triazolgruppe, die bei der Klick-Reaktion entsteht, induziert als Nachahmung von cis-Prolin eine Kehre. [39] Pseudoproline [40] und Heterocyclen [41] wurden ebenfalls genutzt, um Kehrenstrukturen in cyclische Peptide einzuführen.…”
Section: Cyclische Peptidkehrenunclassified